Multisystemic Sarcoidosis Presenting With Leg Ulcers, Pancytopenia, and Polyserositis Was Successfully Treated With Glucocorticoids: A Case Report and Literature Review - Qiao, Xin; He, Shan; Altawil, Abdullah; Wang, Qiu-yue; Kang, Jian; Li, Wen-yang; Yin, Yan (Frontiers in Medicine, 2022)
Introduction: Sarcoidosis is a chronic granulomatous disease of unknown aetiology. A variety of studies have pointed out that almost every part of the body can be affected, but it most often affected the lungs and intrathoracic lymph nodes. However, cases of sarcoido-sis involving multiple organs in one patient are rarely reported. We describe a unique case of sarcoidosis, which was characterized by multiorgan involvement, including leg ulcers, splenomegaly, pancytopenia, and polyserositis. Glucocorticoids were effective during the treatment of the above lesions. This case highlights the diversity of clinical manifestations of sarcoidosis, and emphasizes the im-portance of its differential diagnosis and the periodical follow-up. These are crucial to physicians in the diagnosis and treatment of sarcoidosis. Main symptoms and important clinical findings: A 30-year-old male complained about intermittent fever three years ago. A computed tomographic scan of the chest showed lymphadenopathy in the mediastinum and hilar regions. Routine blood tests showed leu-kopenia and mild anaemia. The pathologic result of mediastinal lymph node biopsy was granulomatous lesions; thus, the patient was diagnosed with type II sarcoidosis without glucocorticoid therapy. In the following two years, the patient suffered from intermittent fever accompanied by dyspnea, fatigue, occasional cough, less sputum, and apparent weight loss. Abnormal physical examinations in-cluded leg ulcers and splenomegaly. Laboratory and physical tests revealed pancytopenia, polyserositis and enlargement of lymph nodes. The pathological findings of leg ulceration, pleura and left supraclavicular lymph node all suggested granulomas. Diagnosis, interventions and outcomes: It strongly suggested sarcoidosis since tuberculosis, lymphoma and connective tissue disease were all excluded. Due to severe conditions and multiorgan involvement, we tried to provide methylprednisolone for this patient. After nine months of oral glucocorticoids therapy, his subjective symptoms as well as haematological and radiological findings were all im-proved. His leg skin ulceration and scab were also completely disappeared. Conclusions: Sarcoidosis has diverse clinical presentations, and many patients present with atypical symptoms. It needs to be timely identified by the clinician, and carefully differentiated from other diseases with similar findings, so as to make an accurate diagnosis.